The mirror of Great Britain : a life of King James VI & I - Jackson, Clare, 1972- (Liverlight, an imprint of W.W. Norton & Company, 2025)
"History has not been kind to King James. A cradle king who was crowned in Scotland in 1567 and England and Ireland in 1603, James VIand I has long been eclipsed in fame and reputation by his predecessor and cousin, Elizabeth I, and his mother, Mary, Queen of Scots. Now, four hundred years after his death, Wolfson History Prize-winning historian Clare Jackson finally reappraises the life and legacy ofthe 'first king of Great Britain.' Beginning with the surprise assassination of his father, Lord Darnley, and the subsequent beheading of his mother, Jackson contextualizes the tempest of James's childhood as well as the many attempts on his life, from his teenage detention by the Ruthven Raiders to the infamous Gunpowder Plot of 1605. So, too, does she consider the renewed creativity of the Jacobean era, culminating in the King James Bible, Macbeth, and King Lear, and demonstrates how the king's keen interest in joining worlds old and new -- establishing colonies overseas and, closer to home, uniting Scotland, England, and Ireland -- set the geopolitical stage for centuries to come. In so doing, Jackson reveals King James as perhaps themost consequential monarch of the early modern era, whose impact, for better and for worse, still reverberates today."--